Focused Ultrasound Enhances Brain Delivery of Sorafenib Nanoparticles. Issue 2 (21st December 2022) - Dahis, Daniel; Azagury, Dana Meron; Obeid, Fadi; Dion, Michelle Z.; Cryer, Alexander M.; Riquelme, Mariana Alonso; Dosta, Pere; Abraham, Ariel William; Gavish, Moshe; Artzi, Natalie; Shamay, Yosi; Azhari, Haim
Abstract : Glioblastoma (GBM) is a universally lethal form of brain cancer. The success of novel treatments is hindered by the blood–brain barrier (BBB), which prevents most drugs from penetrating GBM tumors. Sorafenib (SFB), a proapoptotic multikinase inhibitor, has been investigated for the treatment of GBM; however, survival benefit among patients has not improved. Recently, an indocyanine‐stabilized nanoparticulate form of SFB (SFB NPs) with improved tumor accumulation was developed in comparison to SFB alone. Herein, the benefit of SFB NPs and focused ultrasound (FUS)‐mediated BBB disruption is assessed to enable noninvasive, safe, and reversible BBB permeation for enhanced SFB NPs brain accumulation. Treatment of SFB NPs and FUS yields lower IC50 values (2.7 and 29 μm in 2D and 3D U87 cell models vs 7.5 and 37.1 μm for SFB NPs alone). SFB NPs and FUS with microbubbles improve SFB NPs uptake by U87 cells compared to SFB NPs alone (46% increase; p = 0.0123). In vivo, FUS enhances SFB NPs brain accumulation by 2.5‐fold compared to the contralateral hemisphere, and 3.6‐fold compared to unsonicated brains. In conclusion, SFB NPs are a promising agent for GBM treatment and its therapeutic capacity can be potentially enhanced when combined with FUS‐mediated BBB disruption. Abstract : Sorafenib (SFB) stabilization into IR783‐containing nanoparticles (NPs) retains SFB cytotoxicity, and improves its aqueous solubility and theranostic use. Focused ultrasound sonication with microbubbles increases SFB NPs blood–brain barrier penetration, and improves uptake in brain cancer cells. This work reveals a SFB‐based theranostic formulation for brain cancer treatment and its enhanced accumulation in the brain using focused ultrasound.